Optimization of the marinating conditions of cassava fish (Pseudotolithus sp.) fillet for Lanhouin production through application of Doehlert experimental design - Kindossi, Janvier Mêlégnonfan; Anihouvi, Victor B.; VIEIRA ÉPSE DALODE, A. GÉNÉROSE E. MARIE; AKISSOE, H. NOËL; HOUNHOUIGAN, DJIDJOHO JOSEPH (My University, 2015)
Lanhouin is a traditional fermented salted fish made from the spontaneous and uncontrolled fermentation of whole salted cassava fish (Pseudotolithus senegalensis) mainly produced in the coastal regions of West Africa. The combined effects of NaCl, citric acid concentration, and marination time on the physicochemical and microbiological characteristics of the fish fillet used for Lanhouin production were studied using a Doehlert experimental design with the objective of preserving its quality and safety. The marination time has significant effects on total viable and lactic acid bacteria counts, and NaCl content of the marinated fish fillet while the pH was significantly affected by citric acid concentration and marination duration with high regression coefficient R2 of 0.83. The experiment showed that the best conditions for mari nation process of fish fillet were salt ratio 10 g/100 g, acid citric concentration 2.5 g/100 g, and marination time 6 h. These optimum marinating conditions obtained present the best quality of marinated flesh fish leading to the safety of the final fermented product. This pretreatment is necessary in Lanhouin production processes to ensure its safety quality
Keywords: Citric acid; fish fillet; Lanhouin; marination; optimization; salt